HYPOGLYCEMIC EFFECT OF TRIGONELLINE ISOLATED FROM IRAQI FENUGREEK SEEDS IN NORMAL AND ALLOXAN-DIABETIC RABBITS - Al-Khateeb, Ekbal; Hamadi, Salim A.; Al-Hakeemi, Adeeb A.N.; Abu-Taha, May; Al-Rawi, Naseer (European Scientific Journal, ESJ, 2012)
﻿Fenugreek (trigonella foenum graecum) is one of the most widely used medicinal plants in folk medicine. It is known to have a diuretic, cardio tonic, hypotensive, hypoglycemic and hypolipidemic effect. This study was designed to evaluate the hypoglycemic effect of Trigonelline isolated from Iraqi fenugreek seeds in normal and alloxan –diabetic rabbits. Sixty male adult albino rabbits were used in this study. They were divided randomly into two main groups, a non-diabetic group (group A) and a diabetic group (group B). The two groups were further subdivided into subgroups, A1 - A4 and B1 – B5. Group A1 & B1 were control. Group A2 & B2, A3 , B3 and A4 & B4 were received orally 10mg/12hrs isolated pure trigonelline, 10mg/12 hrs standard Trigonelline and 7.7ml/12hrs ethanol extract of the fenugreek seeds respectively, while group B5 received insulin. The data revealed that the isolated pure trigonelline exhibited a significant (P < 0.05) hypoglycemic effect in normal and diabetic rabbits, but its effect is more profound in diabetic groups. Isolated pure trigonelline reduces blood glucose level by 21.3% in the non-diabetic group and 27.53% in the diabetic group. The result of this study also indicated that the hypoglycemic effect of ethanol extract of fenugreek seeds and that of isolated pure trigonelline was not significant (P >0.05 ). In conclusion, based on the result of this study, trigonelline at a dose of 10mg/12hrs has a significant hypoglycemic effect in both normal and diabetic rabbits. It is preferred to use trigonelline to avoid the possible adverse reactions which may appear due to the multi-components of the ethanol extract of the fenugreek seeds.